Sphenopalatine artery pseudoaneurysm after assault by a firearm in the face (Research, Society and Development, 2020)
Because of their location, sphenoplatin artery pseudoaneurysms (PAS) are extremely rare. Its formation is from a partial rupture of the endothelium, resulting in blood leakage in the surrounding tissues. Here, we report this case of PAS after assaulting the face by a firearm projectile, followed by uncontrollable epistaxis. It is important that professionals be aware of this unusual complication of facial trauma and alternatives for the treatment of pseudoaneurysms. Embolization provides a safe and effective method for the treatment of these vascular lesions.